Representação discursiva de Dilma Rousseff em editoriais da Folha de São Paulo no processo de impeachment (03/12/2015 a 01/01/2016) - Lima, Tatiana de Souza (2024)
The research we undertook examines the construction of the discursive representation of former president Dilma Rousseff in Folha de S. Paulo’s editorials in the first month of the impeachment process against her. The process began with the acceptance of the request by the then president of the Chamber of Deputies, Eduardo Cunha, on December 2, 2015. The texts that are part of the corpus of the research were published between December 3, 2015 and January 2, 2016. It is a study that focuses on the semantic level of the text, within the approach of Textual Analysis of Discourses; it is also a proposal for analysis focusing on the levels of textual structuring, especially at the microtextual level. Editorials are texts belonging to the opinion section of newspapers, through which the journalistic company presents its point of view on what is happening in the country. Thus, the general objective was to identify which elements the newspaper used to construct the discursive representation of Dilma Rousseff in this fundamental period in recent history: the first month of the process of deposing the first elected president of Brazil. Thus, we asked the following question: Folha de S. Paulo, through its editorials, constructed which discursive representation of Dilma in the first month of the impeachment process? From the corpus formed by Folha de S. Paulo’s twelve editorials, we identified, described and interpreted the words used in the editorials according to the semantic categories of referencing, predication and modification. We inserted the results in tables that describe each of the categories. Concomitantly, we selected the clauses with mentions to Dilma and others nouns related to her; this selection resulted in a text formed by 147 (one hundred and fortyseven) clauses. One of the theoretical implications verified is that the corpus, after this analysis, corresponds, in fact, to the propositional content to which Adam (2011) alludes and which constructs the discursive representation of Dilma formulated by Folha de São Paulo. In addition, we understand that the advancement of analysis at the microtextual level has improved the analysis of the "whole of meaning" that makes the unity of the text (Adam, 2022). In practice, we understand that editorials are a discursive genre capable of demonstrating the position taken by communication means within the context of media discourse. And, based on the discourse formulated by Folha de S. Paulo in the period, we could affirm that the newspaper elaborated its discourse based on three semantic pillars: political dispute; economic crisis; Dilma's mistakes and agony. These themes were observed in referrers, in predicators and modifiers.In conclusion, we observe that Folha de S. Paulo constructed a discursive representation of Dilma according to which the former president was equated with abstract concepts such as government and Planalto; that, when she was personally cited, she was responsible for aggravating the economic crisis, as she did not have the capacity to make the right decisions; and that the political crisis could be solved by impeachment.